An interaction mode of N-(decyloxyphenyl)-N‘-(4chlorobenzoyl)thiourea dopant in carboxymethyl cellulose (CMC) for solid polymer electrolyte - Khairul W.M.; Ghazali S.R.; Isa M.I.N.; Daud A.I.; Rahamathullah R. (Deuton-X Ltd, 2024)
Indexed by SCOPUS/ERA